Fiscal regimes and the (non)stationarity of debt - Josef Hollmayr (Deutsche Bundesbank, 2018)
This paper analyzes the sustainability of fiscal debt contingent on fiscal policy operating in two fiscal regimes. The first regime is characterized by active policy (not reacting to debt) and the other by passive fiscal policy (reacting to debt). The average duration for which either regime can be pursued in order to arrive at a long-run stable solution is dependent on the steady-state debt-to-GDP ratio and thus determines the cutoff point beyond which debt is non-stationary. We find that the longer an active policy regime is in force or, equivalently, the more likely fiscal policy is to remain in this regime, the lower the steady state debt-to-GDP ratio must be. This has repercussions for the overall business cycle, implying a higher volatility of inflation and output the longer fiscal policy is active for any given equilibrium debt-to-GDP level. Using the Markov-switching DSGE-model as the data generating process it is possible to apply the test by Bohn (1998) and find that it is prone to type 2 errors.
Keywords: C62; E61; E62; 330; DSGE; Markov-Switching; Fiscal Policy; Debt Sustainability